(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
One Of The Greatest Privileges Of Islamic Jurisprudence (Fiqh) Is The Flexibility That Adapt It To Cope With New Events At Different Times And Places. This Flexibility Is Clearly Demonstrated In The Change Of Judgments Following The Change Of Their Causes; And That Is The Jurists Definition Of Jurisprudence Changes. Not Every Judgment Can Be Changeable Besides The Change Cannot Be Governed By Human Whims And Emotions. The Core Of Change Is To Realize What The Lawmaker (Allah) Wants. Thus Our Study Comes To Determinate The Limits Of This Kind Of Judgments By Drawing A Permitted Area For Changes In Islamic Jurisprudence, And Clarify Causes That Lead To Change In Judgments, And Highlight What Controls The Change Of Islamic Fiqh Ijtihad. Key Words - Fiqh, Changeable , Constant, Controls, Ijtihad